Hearing Aid Adoption in the OTC Hearing Aid Era: Market Trends and Consumer Insights from MarkeTrak 2025 - Jilla, Anna Marie; Jorgensen, Lindsey (Seminars in Hearing, 2025)
The 2025 iteration of the MarkeTrak survey offers a comprehensive analysis of hearing aid adoption trends in the United States, with a particular focus on the impact of over-the-counter (OTC) hearing aids introduced in 2022. This study explores evolving consumer behaviors, demographic shifts, and clinical and psychosocial factors influencing hearing aid uptake. Findings reveal a continued increase in overall adoption rates, with OTC devices serving as a critical access point for first-time users—particularly younger, more diverse, and cost-sensitive populations. Despite the affordability and accessibility of OTC devices, traditional hearing aids remain the preferred choice among individuals with more severe hearing loss and those seeking professional support. The report highlights key differences in service delivery, satisfaction, and repurchase intentions between user groups, underscoring the enduring value of professional care. Additionally, the emergence of hearing improvement features in consumer electronics, such as earbuds, signals a broadening of the hearing device landscape. These insights have significant implications for clinical practice, marketing strategies, and policy development, emphasizing the need for flexible, patient-centered care models that accommodate diverse consumer pathways and preferences.
Keywords: hearing aids; OTC; consumer satisfaction